2003
DOI: 10.1021/ja0349002
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic Guest in a 24+ Cationic Host

Abstract: A new tetrahedral coordination cage M12L6 was prepared from a linear dipyrimidine ligand (L) and cis-protected palladium(II) (M). This cage showed unprecedented host-guest chemistry where the cationic host accommodated a cationic guest despite 24+ charges on the host framework. The unusual cation-cation host-guest chemistry is described by a unique onionlike shell structure of the host-guest complex where two cationic spheres are mediated by an anionic sphere of a counteranion assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 13 publications
2
49
0
Order By: Relevance
“…6), could even host one cationic guest molecule NBu 4 + , upon exposure to an excess of [NBu 4 ](BF 4 ). 15 The host-guest complex could be seen as a triple-layer onion-like structure, in which an anionic sphere of BF 4 − ions is mediated between cationic host and guest. No encapsulation was observed in absence of BF 4 − , indicating a clear role of the anion in the encapsulation process.…”
Section: Encapsulation Of Guest Moleculesmentioning
confidence: 99%
“…6), could even host one cationic guest molecule NBu 4 + , upon exposure to an excess of [NBu 4 ](BF 4 ). 15 The host-guest complex could be seen as a triple-layer onion-like structure, in which an anionic sphere of BF 4 − ions is mediated between cationic host and guest. No encapsulation was observed in absence of BF 4 − , indicating a clear role of the anion in the encapsulation process.…”
Section: Encapsulation Of Guest Moleculesmentioning
confidence: 99%
“…[17,18] In some cases, the assembled aggregate is large enough to act as a capsule and completely encapsulate both ions of the salt. [19] A related design is the so-called "venus fly trap" capsule. An example of this design was recently reported by Atwood and coworkers, who showed that an extended, deep-cavity resorcinarene derivative can completely encapsulate a NMe 4 + cation with a Cl -anion positioned by hydrogen bonding at the capsule entrance (see schematic receptor 12).…”
Section: Ditopic Receptors For Associated Ion-pairsmentioning
confidence: 99%
“…3 Here, we report an 8-shaped discrete porous Cu(II) supramolecule constructed by a derivative of salicylic acid and Cu(AcO)2. All chemicals used were of analytical regent grade and were used directly without further purification.…”
mentioning
confidence: 99%